2021
DOI: 10.1155/2021/9970019
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Measuring Thiopurine Metabolites in Children with Inflammatory Bowel Disease and Autoimmunological Hepatitis, Treated with Azathioprine

Abstract: Introduction. Thiopurines, such as azathioprine (AZA) and 6-mercaptopurine (6-MP), are immunomodulatory agents, used for the maintenance of remission in children with inflammatory bowel disease (IBD)—Crohn’s disease (CD) and ulcerative colitis (UC), as well as with autoimmunological hepatitis (AIH). Measurements of thiopurine metabolites may allow identifying patients at risk for toxicity and nonadherence. It can also provide an explanation for the ineffectiveness of the treatment, observed in some patients. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In an interesting study, Bąk-Drabik et al . [ 9 ] evaluated the usefulness of measuring thiopurine metabolites in children with inflammatory bowel disease and autoimmune hepatitis treated with azathioprine. Bąk-Drabik et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting study, Bąk-Drabik et al . [ 9 ] evaluated the usefulness of measuring thiopurine metabolites in children with inflammatory bowel disease and autoimmune hepatitis treated with azathioprine. Bąk-Drabik et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bąk-Drabik et al . [ 9 ] found that patients with 6-TG concentrations ranging from 230 to 450 pmol/8 × 10 8 RBC exhibited higher remission rates than the under- or overdosed patients. At the same time, the authors also emphasized that an optimal therapeutic 6-TG level for AIH was not determined [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation